Copper-aluminum-copper composite material and processing method and application thereof

By controlling the cold rolling processing rate and combining step-by-step annealing treatment, the surface corrugation problem caused by the difference in material ductility during the cold rolling process is solved, and the flat and smooth surface and conductive properties of the copper-aluminum-copper composite are achieved. Improvement.

CN119456665APending Publication Date: 2025-02-18ZHEJIANG XINBANG NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411520420.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the cold rolling process, the surface corrugation of existing copper-aluminum-copper composite materials has caused uneven surface corrugation due to the difference in ductility of copper and aluminum materials, which affects the conductivity.

Method used

By controlling the single-pass processing rate of cold rolling between 3-8%, combined with step-type intermediate annealing treatment, segmented annealing is performed under a protective atmosphere, and slow cooling and cool down to restore the molecular grain structure.

Benefits of technology

The surface twists and ripple caused by the extension inconsistency of the layer are effectively reduced, and a flat and smooth copper-aluminum-copper layer structure is obtained, which improves the conductivity by more than 20%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456665A_ABST
    Figure CN119456665A_ABST
Patent Text Reader

Abstract

The invention relates to a copper-aluminum-copper composite material and a processing method and application thereof, and the processing method comprises the following steps: (1) carrying out cold rolling on a copper-aluminum-copper blank, controlling the single-pass processing rate of cold rolling to be 3-8%, and controlling the total processing rate of a cold rolling single process to be not more than 30%; wherein the copper-aluminum-copper blank comprises a copper layer, an aluminum layer and a copper layer which are stacked in sequence; (2) carrying out annealing treatment on the copper-aluminum-copper blank after the cold rolling single process; the annealing treatment process comprises the following steps: annealing in a protective atmosphere, keeping the temperature at 450-480 DEG C for 1-3 hours in the first stage, keeping the temperature at 310-330 DEG C for 2-4 hours in the second stage, and cooling in a slow cooling manner for 6-8 hours from the first stage to the second stage; and (3) the steps (1) and (2) are repeated until the copper-aluminum-copper composite material with the target thickness is obtained, and surface cleaning is conducted. According to the invention, surface zigzag ripples caused by inconsistent extension of the layer can be greatly reduced, a molecular grain structure is recovered by combining stepped intermediate annealing, and the conductivity of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material processing, and in particular relates to a copper-aluminum-copper composite material and a processing method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles and energy storage industries, battery packs and battery groups are becoming heavier, larger, and charging time shorter; higher requirements are put forward for the conductive connection and lightweight of battery packs. Copper-aluminum composite materials can be used for soft connections of electric vehicles, replacing the original pure copper soft connectors to make the components lighter and reduce material costs at the same time; they can also be used for cable shielding tapes, replacing pure copper foil shielding tapes. Copper-aluminum composite materials are formed by polymer diffusion welding, and have the characteristics of softness, lightness, and high conductivity. Compared with pure copper, they can reduce weight by 50%, reduce costs by 30%, and maintain conductivity, current carrying capacity, and temperature rise. The main uses include automotive batteries, energy storage batteries, battery packs, high and low voltage electrical appliances, vacuum electrical appliances, mining explosion-proof switches, locomotive cabinets, bus ducts, industrial electric furnaces, electrolytic smelting welding equipment, rectifier equipment, and static and dynamic connections of related products.

[0003] Cold rolling is a metal processing method for rolling metal materials. It is a treatment process for processing, thinning and surface finishing of metal materials such as copper, aluminum and steel. During the cold rolling process, the material is plastically deformed by rolling, drawing and other means, so that the material has a higher density and finer grains, thereby improving the mechanical properties and toughness of the material, improving the surface quality of the material, and improving the electrical conductivity and thermal conductivity of the material; the grain size of the annealed after cold rolling deformation is related to many factors, such as the size of the initial grains, the degree of grain fragmentation during the processing, the annealing temperature and time, etc. During the annealing process, the growth of the grains is affected by energy excitation and atomic diffusion. At high temperatures, the diffusion rate of the number of atoms increases, and the energy excitation of the grain boundaries is also enhanced. These factors jointly promote the growth of the grains. Generally speaking, the smaller the initial grains, the slower the grain growth rate and the finer the grains formed. When the grains begin to grow, the atoms in the small grains will gather towards the large grains. Therefore, the faster growing grains consume more atoms than the slower growing grains, and the larger the grains formed in the end. In addition, during the heat treatment annealing of the bimetallic composite material, the outer layer metal absorbs heat energy and transfers it to the middle layer metal to control the grain size of the middle layer aluminum material. The presence of intermetallic substances such as metal alloy layers will also affect the grain growth process.

[0004] The copper-aluminum composite material prepared by continuous casting and rolling or oxygen-free hot rolling process can meet the market requirements of various thickness specifications and different composite ratios after high-precision cold rolling. It has the advantages of stable quality, strong conductivity, light density, large current bearing, small resistance value, high cost performance, etc. In particular, copper-aluminum-copper composite materials are gradually applied to the high-conductor industry under the principle of current skin effect. The current skin effect is a phenomenon that when the current passes through the conductor, the current is mainly concentrated on the surface of the conductor, while the current inside the conductor is small. However, the copper-aluminum-copper composite materials provided by the market have uneven surface ripples due to the different sizes of copper and aluminum rolling deformation during the production and processing process. Therefore, the current skin effect principle causes the material's conductivity to drop sharply during use; in addition, the existing cold rolling single-pass deformation rate is usually 20-40%, and the total processing deformation rate reaches about 70% for intermediate annealing, resulting in serious ripples on the copper and aluminum surfaces, which not only affects the appearance but also reduces the material's conductivity. Summary of the invention

[0005] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to at least solve one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a copper-aluminum-copper composite material and a processing method thereof that meet one or more of the above-mentioned needs.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] A method for processing a copper-aluminum-copper composite material comprises the following steps:

[0008] (1) cold rolling a copper-aluminum-copper billet, controlling a single cold rolling process rate of 3 to 8%, and controlling a total cold rolling process rate of no more than 30%; wherein the copper-aluminum-copper billet comprises a copper layer, an aluminum layer and a copper layer stacked in sequence;

[0009] (2) annealing the copper-aluminum-copper billet after the cold rolling process; wherein the annealing process comprises: annealing under a protective atmosphere, keeping the temperature at 450-480° C. for 1-3 hours in the first stage, keeping the temperature at 310-330° C. for 2-4 hours in the second stage, and cooling the temperature from the first stage to the second stage by slow cooling for 6-8 hours;

[0010] (3) Repeat the above steps (1) and (2) until the copper-aluminum-copper composite material of target thickness is obtained and the surface is cleaned.

[0011] As a preferred solution, the chemical composition of the copper layer includes: Zn≤0.006%, Pb≤0.0005%, Sn≤0.0003%, P≤0.0003%, Fe≤0.0008%, Ni≤0.0025%, and the rest is Cu;

[0012] The chemical composition of the aluminum layer includes: Si≤0.25%, Cu≤0.05%, Mn≤0.03%, Fe≤0.3%, Zn≤0.05%, Ti≤0.02%, and Al≥99.6%.

[0013] As a preferred solution, the copper-aluminum-copper billet is a strip with a thickness of 3.00 to 7.00 mm and a width of no more than 1050 mm.

[0014] As a preferred embodiment, in step (1), the diameter of the cold rolling roll is 400-450 mm, and the unit speed is 30-50 m / min.

[0015] As a preferred solution, in step (3), a low-temperature degreasing agent is used for surface cleaning, the concentration of the degreasing agent is 8 to 12%, and the cleaning speed is 25 to 30 m / min.

[0016] The present invention also provides a copper-aluminum-copper composite material obtained by processing using the processing method described in any of the above schemes.

[0017] As a preferred embodiment, the distance between the crest and the trough of the surface corrugations of the copper-aluminum-copper composite material is 0.5 to 2 μm.

[0018] As a preferred solution, the dyne value of the surface of the copper-aluminum-copper composite material is ≥42#.

[0019] As a preferred embodiment, the molecular grains of the copper-aluminum-copper composite material are equiaxed grains with a hexahedral structure.

[0020] The present invention also provides an application of the copper-aluminum-copper composite material as described in any of the above schemes, characterized in that it is used for battery pack connection bars or power connection bars.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention controls the single-pass cold rolling processing rate at 3-8%, which can effectively curb the difference in elongation between copper and aluminum materials, greatly reduce the surface tortuosity and ripples caused by inconsistent elongation of the layer, and combines the step-type intermediate annealing to restore the molecular grain structure, thereby obtaining a smooth and bright copper-aluminum-copper layer structure, while improving the conductivity of the copper-aluminum-copper composite material by more than 20%, and can be widely used in new energy battery pack connecting bars, power connecting bars, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a flow chart of a method for processing a copper-aluminum-copper composite material according to Example 1 of the present invention;

[0024] Figure 2 is an electron microscope image of the surface corrugations of the cold-rolled strip of Example 1 of the present invention;

[0025] Figure 3 is an electron microscope image of the surface corrugations of the cold-rolled strip of Comparative Example 1 of the present invention;

[0026] Figure 4 This is a comparison diagram of the surface corrugations of the cold-rolled strips of Example 1 of the present invention and Comparative Example 1;

[0027] Figure 5 1 and 2. These are the original grain state diagram (a) of the aluminum layer of Example 1 of the present invention, the grain state diagram after processing and deformation (b), and the grain state diagram after annealing treatment. DETAILED DESCRIPTION

[0028] In order to more clearly illustrate the embodiments of the present invention, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings and other implementation methods can be obtained based on these accompanying drawings without creative work.

[0029] Embodiment 1:

[0030] like Figure 1 As shown, the processing method of the copper-aluminum-copper composite material of this embodiment includes the following steps:

[0031] (1) Copper-aluminum-copper billet

[0032] The front material of the copper-aluminum-copper billet in this embodiment is red copper T2, the middle layer material is 1 series conductive aluminum 1060, and the back material is red copper T2. The copper-aluminum-copper billet is T2-1060-T2 strip, and the copper-aluminum-copper thickness ratio is 20%:60%:20% (the copper layer thickness on both sides is the same, and the total copper layer thickness is controlled at 3-45%). The copper-aluminum-copper composite coil has a thickness of 5.00 mm and a width of 900 mm.

[0033] Specifically, the chemical composition of copper T2 is: Zn≤0.006%, Pb≤0.0005%, Sn≤0.0003%, P≤0.0003%, Fe≤0.0008%, Ni≤0.0025%, and the rest is Cu;

[0034] The chemical composition of 1 series conductive aluminum 1060 is: Si≤0.25%, Cu≤0.05%, Mn≤0.03%, Fe≤0.3%, Zn≤0.05%, Ti≤0.02%, Al≥99.6%.

[0035] (2) High-precision cold rolling

[0036] A four-roll high-precision cold rolling mill is used, including an opener / winder and a rolling roll. The working roll diameter of the cold rolling mill is 420 mm, the unit speed is 40 m / min, and the rolling force is 120 tons.

[0037] The single cold rolling process has a processing rate of 4.3%, and the single process is divided into six passes, 5.00mm--4.785mm--4.58mm--4.39mm--4.20mm--4.02mm--3.85mm, and the total processing rate is 23%; Figure 2 and Figure 4 As shown, after cold rolling with a small processing rate, the distance between the crest and the trough of the corrugation on the surface of the strip is 1.63 μm. Compared with comparative example 1, the corrugation is reduced by 94.5%.

[0038] (3) Annealing

[0039] The annealing process in this embodiment adopts a bell-type annealing furnace.

[0040] After cold rolling, the copper-aluminum-copper composite strip is subjected to intermediate heat treatment annealing. The intermediate annealing of the heat treatment adopts a high-temperature segmented layer temperature transfer annealing process to ensure the recovery of grain growth of the aluminum layer. The first section is 470°C, kept warm for 2 hours, the second section is 320°C, kept warm for 3 hours, and then slowly cooled for 6.5 hours, so that the surface copper metal temperature is 465°C and the temperature is gradually transferred to the aluminum layer. The aluminum layer forms equiaxed grains in the range of 172°C. The protective gas in the hood annealing furnace is 75% nitrogen and 25% hydrogen, and the atmosphere in the annealing furnace is less than the vacuum pressure of -0.09MPa.

[0041] (4) Surface cleaning

[0042] The copper-aluminum-copper composite material is surface cleaned after the copper-aluminum-copper composite material reaches the target thickness of the finished product;

[0043] Specifically, a low-temperature degreasing agent, model SELRNA D2202, was used. The degreasing agent concentration was 9%, and the cleaning speed was 28 meters per minute. The residual oil spots and oil films on the surface were cleaned, and the dyne value of the copper-aluminum-copper composite material surface was detected to be 44#.

[0044] The surface of the finished copper-aluminum-copper composite material of this embodiment after high-precision cold rolling, step-type heat treatment annealing and cleaning is smooth and flat, the molecular grains are six-sided rhombus equiaxed grains, the grains are uniform and have a size of 5 to 6 μm, and the material conductivity is 90.6% IACS, as shown in Table 1. Compared with Comparative Example 1, the conductivity is increased by 30.8%.

[0045] The copper-aluminum-copper composite material of this embodiment provides a more superior alloy material in the field of lightweight conductivity and heat dissipation, and can be widely used in new energy battery pack connection bars, power connection bars, etc.

[0046] Embodiment 2:

[0047] The processing method of the copper-aluminum-copper composite material of this embodiment comprises the following steps:

[0048] (1) Copper-aluminum-copper billet

[0049] The front material of the copper-aluminum-copper billet in this embodiment is red copper T2, the middle layer material is 1 series conductive aluminum 1060, and the back material is red copper T2. The copper-aluminum-copper billet is T2-1060-T2 strip, and the copper-aluminum-copper thickness ratio is 20%:60%:20%. The thickness of the copper-aluminum-copper billet is 6.500mm and its width is 720mm.

[0050] Specifically, the chemical composition of copper T2 is: Zn≤0.006%, Pb≤0.0005%, Sn≤0.0003%, P≤0.0003%, Fe≤0.0008%, Ni≤0.0025%, and the rest is Cu;

[0051] The chemical composition of 1 series conductive aluminum 1060 is: Si≤0.25%, Cu≤0.05%, Mn≤0.03%, Fe≤0.3%, Zn≤0.05%, Ti≤0.02%, Al≥99.6%.

[0052] (2) High-precision cold rolling

[0053] A four-roll high-precision cold rolling mill is used, including an opener / winder and a rolling roll. The working roll diameter of the cold rolling mill is 420 mm, the unit speed is 36 m / min, and the rolling force is 135 tons.

[0054] The single cold rolling process has a processing rate of 5.5%. The single process is divided into six passes, 6.500mm--6.140mm--5.800mm--5.280mm--4.98mm--4.7mm, and the total processing rate is 27.7%. After the cold rolling process with a small processing rate, the spacing between the crest and the trough of the corrugation on the surface of the strip is 1.70μm. Compared with Comparative Example 1, the corrugation is reduced by 94.3%.

[0055] (3) Annealing

[0056] The annealing process in this embodiment adopts a bell-type annealing furnace.

[0057] After cold rolling, the copper-aluminum-copper composite strip is subjected to intermediate heat treatment annealing. The intermediate annealing of the heat treatment adopts a high-temperature segmented layer temperature transfer annealing process to ensure the recovery of grain growth of the aluminum layer. The first section is 475°C, kept warm for 2 hours, the second section is 315°C, kept warm for 3 hours, and then slowly cooled for 7 hours, so that the surface copper metal temperature of 472°C is gradually transferred to the aluminum layer, and the aluminum layer forms equiaxed grains in the range of 175°C; the protective gas in the hood annealing furnace is 75% nitrogen and 25% hydrogen, and the atmosphere in the annealing furnace is less than the vacuum pressure of -0.08MPa.

[0058] (4) Surface cleaning

[0059] The copper-aluminum-copper composite material is surface cleaned after the copper-aluminum-copper composite material reaches the target thickness of the finished product;

[0060] Specifically, a low-temperature degreasing agent, model SELRNAD2202, is used. The degreasing agent concentration is 10%, and the cleaning speed is 30 meters / minute. The residual oil spots and oil film on the surface are cleaned, and the dyne value of the copper, aluminum and copper surface is detected to be 42#.

[0061] After high-precision cold rolling, heat treatment annealing and cleaning, the surface of the finished copper-aluminum-copper composite material is smooth and flat, the molecular grains are hexagonal rhombus equiaxed grains, the grains are uniform and the size is 2 to 4 μm, and the material conductivity is 92.05% IACS, as shown in Table 1. Compared with Comparative Example 1, the conductivity is increased by 32.9%.

[0062] The copper-aluminum-copper composite material of this embodiment provides a more superior alloy material in the field of lightweight conductivity and heat dissipation, and can be widely used in new energy battery pack connection bars, power connection bars, etc.

[0063] Comparative Example 1:

[0064] The processing method of the copper-aluminum-copper composite material of this comparative example is different from that of Example 1 in that:

[0065] The processing rate of a single pass is 23%, that is, one pass of cold rolling is 5.00mm--3.85mm; after the high processing rate of cold rolling, the distance between the crest and the trough of the corrugation on the surface of the strip is 30μm. Figure 3 and Figure 4 As shown, this is because the ripples on the copper-aluminum-copper surface are caused by the large difference in ductility between copper and aluminum during the copper-aluminum-copper processing. The two metals are combined into one, the accumulation of the middle aluminum layer cannot be released, and the processing deformation rate is too large. The molecular grains of the material tend to be long strips and the fluctuations are obvious, and the resulting zigzag strips appear on the surface of the material;

[0066] The intermediate annealing of heat treatment adopts the first stage of 315℃, holding temperature for 3 hours, and the second stage of 475℃, holding temperature for 2 hours;

[0067] For other process steps, please refer to Example 1.

[0068] Comparative Example 2:

[0069] The processing method of the copper-aluminum-copper composite material of this comparative example is different from that of Example 1 in that:

[0070] The intermediate annealing of heat treatment adopts the first stage of 315℃, holding temperature for 3 hours, and the second stage of 475℃, holding temperature for 2 hours;

[0071] For other process steps, please refer to Example 1.

[0072] Table 1 Test results of copper-aluminum-copper composite materials of Example 1, Comparative Example 1 and Comparative Example 2

[0073]

[0074] The copper-aluminum-copper composite strip of the present invention is processed by cold rolling with a slight amount of reduction, and the processing rate of a single pass of a cold rolling process is controlled at 3-8%, and the distance between the crest and the trough of the corrugation on the surface of the strip is less than 2 μm; in addition, Figure 5 As shown, the intermediate heat treatment annealing will restore the grains of the copper-aluminum-copper composite strip. The molecular grains of the material are deformed too much due to the work hardening process, gradually tending to be long strips, and the undulations are manifested on the surface of the material; and because the single-pass processing rate is small, the molecular grain structure of the material is not completely broken. The outer layer of the material is copper and the inner layer is aluminum. The heat treatment must adopt a high-temperature segmented layer temperature transfer annealing process to ensure the recovery of the grain growth of the aluminum layer. The first stage is kept at 450-480℃ for 1-3 hours, and the second stage is kept at 310-330℃ for 2-4 hours. The temperature is slowly cooled for 6-8 hours from the first stage to the second stage, and the temperature is transferred to the aluminum layer through the surface copper metal. The aluminum layer forms an equiaxed grain state in the range of 160-180℃, while reducing the difference in ductility between copper and aluminum materials.

[0075] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected according to actual needs within the limited range, and the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the content required to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.

[0076] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A method for processing a copper-aluminum-copper composite material, characterized in that: The following steps are involved: (1) cold rolling a copper-aluminum-copper billet, controlling a single cold rolling process rate of 3 to 8%, and controlling a total cold rolling process rate of no more than 30%; wherein the copper-aluminum-copper billet comprises a copper layer, an aluminum layer and a copper layer stacked in sequence; (2) annealing the copper-aluminum-copper billet after the cold rolling process; wherein the annealing process comprises: annealing under a protective atmosphere, keeping the temperature at 450-480° C. for 1-3 hours in the first stage, keeping the temperature at 310-330° C. for 2-4 hours in the second stage, and cooling the temperature from the first stage to the second stage by slow cooling for 6-8 hours; (3) Repeat the above steps (1) and (2) until the copper-aluminum-copper composite material of target thickness is obtained and the surface is cleaned.

2. The processing method according to claim 1, characterized in that: The chemical composition of the copper layer includes: Zn≤0.006%, Pb≤0.0005%, Sn≤0.0003%, P≤0.0003%, Fe≤0.0008%, Ni≤0.0025%, and the rest is Cu; The chemical composition of the aluminum layer includes: Si≤0.25%, Cu≤0.05%, Mn≤0.03%, Fe≤0.3%, Zn≤0.05%, Ti≤0.02%, and Al≥99.6%.

3. The processing method according to claim 1 or 2, characterized in that: The copper-aluminum-copper blank is a strip with a thickness of 3.00 to 7.00 mm and a width of no more than 1050 mm.

4. The processing method according to claim 1, characterized in that: In the step (1), the diameter of the cold rolling roll is 400-450 mm, and the unit speed is 30-50 m / min.

5. The processing method according to claim 1, characterized in that: In the step (3), the surface is cleaned using a low-temperature degreasing agent with a degreasing agent concentration of 8 to 12% and a cleaning speed of 25 to 30 m / min.

6. The copper-aluminum-copper composite material obtained by the processing method according to any one of claims 1 to 5.

7. The copper-aluminum-copper composite material according to claim 6, characterized in that: The distance between the crest and the trough of the surface corrugation of the copper-aluminum-copper composite material is 0.5-2 μm.

8. The copper-aluminum-copper composite material according to claim 6, characterized in that: The dyne value of the surface of the copper-aluminum-copper composite material is ≥42#.

9. The copper-aluminum-copper composite material according to claim 6, characterized in that: The molecular crystal grains of the copper-aluminum-copper composite material are equiaxed crystal grains with a hexahedral structure.

10. Use of the copper-aluminum-copper composite material according to any one of claims 6 to 9, characterized in that: Used for battery pack connection bars or power connection bars.

Citation Information

Cited By

  • Brass-aluminum brass composite material and preparation method and application of cold compounding of brass-aluminum brass composite material

    CN121244681A